The Threat of Unionization, the Use of Debt, and the Preservation of Shareholder Wealth - Bronars, S. G.; Deere, D. R. (Quarterly Journal of Economics, 1991)
This paper argues that firms use debt to protect the wealth of shareholders from the threat of unionization. Under U. S. labor law the firm cannot prohibit its workers from attempting to form a collective bargaining unit. Debt policy offers a method of reducing the impact of this monopoly right on shareholders. By issuing debt, the firm credibly reduces the funds that are available to a potential union. Empirical evidence that strongly supports this hypothesis is presented.